2004
DOI: 10.1109/jlt.2004.824355
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Counting OTDR for Local Birefringence and Fault Analysis in the Metro Environment

Abstract: Optical time domain reflectometery (OTDR) is one of the most used measurement techniques in the characterization of optical fiber links. In this paper, we present a thorough investigation of an OTDR using a Peltier cooled photon-counting detector at 1.55 um. Due to its superior spatial resolution and the absence of classical dead-zones, it is well suited for detailed, high resolution analysis of problem zones. We give a detailed analysis of its performance, and also demonstrate that a polarization-sensitive ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…Assuming a drift constant in time (for instance due to a slow temperature variation), an optical path difference of 25 nm in 100 µs would lead to an optical path difference of 90 cm per hour. We measured the optical lengths of the two fibers with a high resolution photon counting optical time domain reflectometer [26], and found that the difference remained constant within a few cm over the course of 12 hours (from 1 P.M. to 1 A.M.). This shows that the observed phase noise is most likely due to other causes than a slow thermal drift.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a drift constant in time (for instance due to a slow temperature variation), an optical path difference of 25 nm in 100 µs would lead to an optical path difference of 90 cm per hour. We measured the optical lengths of the two fibers with a high resolution photon counting optical time domain reflectometer [26], and found that the difference remained constant within a few cm over the course of 12 hours (from 1 P.M. to 1 A.M.). This shows that the observed phase noise is most likely due to other causes than a slow thermal drift.…”
Section: Discussionmentioning
confidence: 99%
“…The technique (COTDR) (Wegmuller et al, 2004) is appropriate to detect the defaults in a given fibre (sites of reflection, losses) with a spatial resolution of the decimetre order. The main difference of this reflectometer (Cherbi et al, 2009) compared to a classic OTDR (Ellison & Siddiqui, 1998) resides in the use of photon counting detector (InGaAs avalanche photodiode).…”
Section: Measure Of the Dgd In The Spun Fibres By The C-otdr Methodsmentioning
confidence: 99%
“…The beat length of the fibre can be measured directly by the extraction of the spatial period of the backscattered signals (Wegmuller, 2002(Wegmuller, , 2004, which permits to estimate the PMD in the single-mode fibres (Ellison et al, 1998;. The OFDR method is not exploited again especially for investigating of the spun fibres for the determination of its parameters and of their PMD according to the distance.…”
Section: Determination Of the Polarization's Properties Of The Spun Fmentioning
confidence: 99%
“…10 However, in recent years, other contributions have been reported: (i) the "twilight effect" 11,12 and (ii) the "charge persistence" [13][14][15][16][17][18] (also called "charge subsistence") effect. The former has been noticed in thick-junction silicon SPADs and it consists in an increase of the background noise due to photons absorbed during the hold-OFF time just before the following ON-time.…”
mentioning
confidence: 99%